Dissemination and Implementation of Patient-centered Indicators of Pain Care Quality and Outcomes. Issue 2 (February 2019) - Beck, Susan L.; Dunton, Nancy; Berry, Patricia H.; Brant, Jeannine M.; Guo, Jia-Wen; Potter, Catima; Spornitz, Beth; Eaton, Jacqueline; Wong, Bob
Abstract : Background: Previous approaches to measuring and improving nursing-sensitive, patient-centered metrics of pain quality and outcomes in hospitalized patients have been limited. Methods: In this translational research study, we disseminated and implemented pain quality indicators in 1611 medical and/or surgical, step-down, rehabilitation, critical access, and obstetrical (postpartum) units from 326 US hospitals participating in the National Database of Nursing Quality Indicators. Eligible patients were English-speaking adults in pain. Trained nurses collected patients' perceptions via structured interview including 9 pain quality indicators, demographic, and clinical variables; these patient experience data were merged with unit and hospital level data. Analyses included geographic mapping; summary statistics and 3-level mixed effects modeling. Results: Hospitals in 45 states and District of Columbia participated. Of 22, 293 screened patients, 15, 012 were eligible; 82% verbally consented and participated. Pain prevalence was 72%. Participants were 59.4% female; ages ranged from 19 to 90+ (median: 59 y); 27.3% were nonwhite and 6.5% were Hispanic. Pain intensity on average over the past 24 hours was 6.03 (SD=2.45) on a 0–10 scale. 28.5% of patients were in severe pain frequently or constantly. Race (nonwhite), younger age, being female and nonsurgical were associated ( P <0.001) with greater pain. Care quality indicators ranking lowest related to discussion of analgesic side effects and use of nonpharmacologic approaches. Conclusions: Unrelieved pain remains a high-volume problem. Individual factors and unit type were significantly associated with pain outcomes. Hospitals can employ these quality indicators to direct continuous quality improvement targeting pain care quality. Abstract : Supplemental Digital Content is available in the text.